Theories about capital structure and profitability in companies - Ramírez Huerta, Valiente Pantaleón (2019)
In this research work, we aimed to determine what are the theories about capital structure and profitability that are being applied in companies in Spain and Latin America by setting their permanent funds (capital) search policies, through the documentary analysis of twenty-two published research on the subject between 2005 and 2019. The results show that the theory of compensation is mostly applied, followed by the theory of hierarchical order and third and lastly the theory of Market Independence and Imperfections. The three theories must be harmonized into a single theoretical body since they complement each other.